2017
DOI: 10.5336/biostatic.2017-57306
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Affecting Factors of the Number of Babies Born Alive in Multiple Pregnancies with Poisson Models

Abstract: Objective: Multiple pregnancies occurred more frequently with being widespread of the assisted reproduction techniques. The recent researches showed that the possibility of multiple pregnancies has been increased by some factors such as twin pregnancy experience in the family, mothers at later ages, social properties and the number of live-born infants. The main aim of this study is to identify the statistically significant factors affecting the multiple pregnancies using count data models. Material and Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…In most of demographic studies, the type of data and the response variable dictates the type of modelling to be carried out. For example, Erkan, et al [8] compared Quasi Poisson and Conway-Maxwell-Poisson (COM) regression models in determining the factors affecting the number of babies born alive in multiple pregnancies. The model selection based on Akaike Information Criterion values revealed that COM Poisson model outperformed the Quasi Poisson model.…”
Section: Introductionmentioning
confidence: 99%
“…In most of demographic studies, the type of data and the response variable dictates the type of modelling to be carried out. For example, Erkan, et al [8] compared Quasi Poisson and Conway-Maxwell-Poisson (COM) regression models in determining the factors affecting the number of babies born alive in multiple pregnancies. The model selection based on Akaike Information Criterion values revealed that COM Poisson model outperformed the Quasi Poisson model.…”
Section: Introductionmentioning
confidence: 99%